Binding sites of different geometries for the 16-3 phage repressor - Papp, Péter P. (National Academy of Sciences, 2002)
Prokaryotic repressor–operator systems provide exemplars for the sequence-specific interactions between DNA and protein. The crucial atomic contacts of the two macromolecules are attained in a compact, geometrically defined structure of the DNA–protein complex. The pitch of the DNA interface seems an especially sensitive part of this architecture because changes in its length introduce new spacing and rotational relations in one step. We discovered a natural system that may serve as a model for investigating this problem: the repressor of the 16-3 phage of Rhizobium meliloti (helix-turn-helix class protein) possesses inherent ability to accommodate to various DNA twistings. It binds the cognate operators, which are 5′-ACAA-4 bp-TTGT-3′ (O(L)) and 5′-ACAA-6 bp-TTGT-3′ (O(R)) and thus differ 2 bp in length, and consequently the two half-sites will be rotated with respect to each other by 72° in the idealized B-DNA (64° by dinucleotide steps calculations). Furthermore, a synthetic intermediate (DNA sequence) 5′-ACAA-5 bp-TTGT-3′ (O(5)) also binds specifically the repressor. The natural operators and bound repressors can form higher order DNA–protein complexes and perform efficient repression, whereas the synthetic operator-repressor complex cannot do either. The natural operators are bent when complexed with the repressor, whereas the O(5) operator does not show bending in electrophoretic mobility assay. Possible structures of the complexes are discussed.